Factors affecting household debt to moneylenders - Mustika, Mustika; Hasanah, Neneng; Irfany, Mohammad Iqbal (Annals of Human Resource Management Research, 2023)
Purpose: Moneylenders, sometimes called 'loan sharks' due to their high interest rates, are informal financial institutions that offer loans not in line with Islamic law. This study analyzes the factors that influence the behavior of households regarding debt to moneylenders. Research Methodology: This research employs descriptive and logistic regression analyses using primary data collected from locals in Jagapura village, Cirebon. Result: The results indicate that basic household necessities determine their debt behavior. However, Islamic financial literacy and increasing income present effective solutions for moneylenders to overcome their debt. Limitation: This study is based on primary data from a specific village, Jagapura, in Cirebon, which may not be representative of all households in debt to moneylenders in other regions or settings. Contribution: The study suggests that Islamic financial institutions should assist unbankable communities needing funds for daily expenses by performing social functions such as offering interest-free loans (qardhul hasan) and providing Islamic social finance. The establishment of sharia compliant savings and loans could also be a solution to usury-related issues.